Effectiveness of principals’ supervision and the learning performance of high school teachers through digital-based PLC - Hastuti, Rita; Johar, Permana; Taufani (Universitas Jambi, Indonesia, 2025)
Teachers' learning performance can be improved through the principal's supervision by implementing several strategies and supporting tools. One of the strategies in learning supervision can be carried out through digital-based Professional Learning Communication (PLC) activities. The purpose of this study is to analyze the effectiveness of learning supervision in improving teacher learning performance through digital-based PLC activities, using a quantitative method with a multiple-regression research design. The results showed that the adjusted R2 (determination coefficient) was 0.934, meaning that the supervision activity of digital-based PLC (X1), and the supervision outcome activity of digital-based PLC (X2) contributed 93.4%, to the improving the learning performance of high school teachers (Y), while the remaining 6.6% explained by other factors that are not described in this study. The result of F (418.635) > F-table (3.91) and the significance value of P = 0.001 < α 0.05, means that the test model is feasible. In other words, there is a significant simultaneous influence of both variables on the improvement of high school teachers' learning performance (Y).